Manajemen Peserta Didik dalam Pembinaan Perilaku Keberagamaan - Diantoro, Fery (IAIN Ponorogo, 2018)
Religious behavior becomes an important point that is very fundamental to be owned by every student, because this is closely related to the attitudes and behaviors that will be demonstrated by students in their daily life. Therefore, the schools should be able to present good behavior and religious attitudes to students. Religious behavior coaching is the process of behavior formation, morality and character for students to stock the present and future life. Behavior coaching of students into the work domain of the student management. The school must manage the students well to create students that are in accordance with what has been expected and aspired. In this study using a descriptive qualitative approach, describe the student management in the religious behavior coaching in MTs Al-Burhan Watulimo. With the findings consists of students orientation activities, the worship habituation, reading Al-Quran, scientific and Islamic studies, and guidance of discipline and character.ÙØµØ¨Ø Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙØ·Ø© Ù ÙÙ Ø© Ø¬Ø¯Ø§ Ø£Ù ØªÙÙÙ Ù Ù ÙÙÙØ© Ù Ù ÙØ¨Ù ÙÙ Ø§ÙÙ ØªØ¹ÙÙ Ø ÙØ£Ù ÙØ°Ø§ ÙØ±ØªØ¨Ø· Ø§Ø±ØªØ¨Ø§Ø·Ø§ ÙØ«ÙÙØ§ Ø§ÙÙ ÙØ§ÙÙ ÙØ§ÙØ³ÙÙÙÙØ§Øª Ø§ÙØªÙ Ø³ÙØªÙ Ø¥Ø«Ø¨Ø§ØªÙØ§ Ù Ù ÙØ¨Ù Ø§ÙÙ ØªØ¹ÙÙ ÙÙ ÙÙ ØÙØ§ØªÙÙ Ø§ÙÙÙÙ ÙØ©. ÙØ°ÙÙØ ÙÙØ¨ØºÙ Ø£Ù ØªÙÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© ÙØ§Ø¯Ø±Ø© Ø¹ÙÙ ØªÙØ¯ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¬ÙØ¯ ÙØ§ÙÙ ÙØ§ÙÙ Ø§ÙØ¯ÙÙÙØ© ÙÙÙ ØªØ¹ÙÙ ÙÙ. ØªÙØ¬ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙ Ø¹Ù ÙÙØ© ØªØ´ÙÙÙ Ø§ÙØ³ÙÙÙ ÙØ§ÙØ£Ø®ÙØ§Ù ÙØ§ÙØ·Ø§Ø¨Ø¹ ÙÙÙ ØªØ¹ÙÙ ÙÙ ÙØªØ®Ø²Ù Ø§ÙØÙØ§Ø© Ø§ÙØØ§ÙÙØ© ÙØ§ÙÙ Ø³ØªÙØ¨ÙÙØ©. ØªÙØ¬ÙÙ Ø³ÙÙÙ Ø§ÙÙ ØªØ¹ÙÙ ÙÙ ÙÙ Ù Ø¬Ø§Ù Ø¹Ù Ù Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙ ØªØ¹ÙÙ ÙÙ. ÙØ¬Ø¨ Ø¹ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙ ØªØ¹ÙÙ ÙÙ Ø¨Ø´ÙÙ Ø¬ÙØ¯ ÙØ®ÙÙ Ø§ÙÙ ØªØ¹ÙÙ ÙÙ Ø§ÙØªÙ ØªØªÙØ§ÙÙ Ù Ø¹ Ù Ø§ ÙØ§Ù Ù ØªÙÙØ¹Ø§ ÙØªØ·ÙØ¹Ø§. ÙÙ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§Ø³ØªØ®Ø¯Ù Ø§ÙÙ ÙÙØ¬ Ø§ÙÙØµÙÙ Ø§ÙÙÙØ¹ÙØ ÙØµÙ Ø¥Ø¯Ø§Ø±Ø© Ø§ÙÙ ØªØ¹ÙÙ ÙÙ ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«ÙØ§ÙÙØ©